Dampak Keberadaan Tempat Pembuangan Akhir Terhadap Kondisi Lingkungan Masyarakat - Katrin Almeisa; Surdin; La Ode Hadini; Sitti Kasmiati (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Final disposal site (landfill) is a physical means of ending the process of waste. The process of storing and destroying at a landfill site has positive and negative impacts. This research aims to determine the impact of the existence of a landfill on the physical and social environmental conditions of the community around KB Village, Puuwatu Village, Puuwatu District. The method used in this research is qualitative descriptive research. The results of this research show: 1) there is an influence of the presence of a landfill on physical environmental conditions on air pollution parameters in the form of the smell of rubbish and dust from rubbish trucks; and 2) there is an influence of the existence of the TPA on the social environmental conditions of the KB village community on communication activities and social interactions of the community.